Ethnobotanical Study of Medicinal Plants Used to Treat Malarial Infections by the Marakwet Community in Kenya - Rotich, C.; Makwali, J.; Ngeiywa, M.; Bowen, A. (Africa Environmental Review Journal, 2022)
Malaria continues to have a devastating impact on public health in Kenya. Resistance to conventional antimalarial drugs is a threat to the treatment of malaria. Globally, medicinal plants have been used to treat malaria for a long time. The objective of this study was to carry out an ethno- botanical survey to identify medicinal plants used to treat malaria in Marakwet East Sub County. The ethno botanical survey was conducted in Marakwet East Sub County from October, 2020 to August, 2021 through oral interviews using structured questionnaires. The plant materials reported by the traditional practitioners were collected, and further authenticated in the laboratory at the department of Biological Sciences University of Eldoret, where voucher specimens were deposited at the departmental herbarium. The results showed that thirty one medicinal plants belonging to twenty four botanical families are used to treat malaria in Marakwet East Sub County. Capparaceae and Rutaceae were the most preferred families while Ximenia americana, Boscia coriacea, were the most frequently used plant species to treat malaria in Marakwet East Sub County. The results of the current study showed that traditional knowledge still plays an important role in the management of malaria in Marakwet East Sub County.